Maternal dietary folate intake with folic acid supplements and wheeze and eczema in children aged 2 years in the Japan Environment and Children’s Study - Hideyuki Masuda; Sumitaka Kobayashi; Chihiro Miyashita; Sachiko Itoh; Yu Ait Bamai; Yasuaki Saijo; Yoshiya Ito; Reiko Kishi; Atsuko Ikeda-Araki; Japan Environment and Children’s Study (JECS) Group (PLoS ONE, 2022)
Maternal intake of folic acid supplements is reportedly associated with the risk of early-onset allergies in offspring. However, only a few studies have considered the intake of both folic acid supplements and dietary folate. Here, the relationship between maternal intake of folic acid supplements and allergic symptoms such as wheeze and eczema in offspring was analyzed while considering dietary folate intake. We examined 84,361 mothers and 85,114 children in the Japan Environment and Children’s Study. The participants were divided into three groups depending on maternal folic acid supplementation (“no use,” “occasional use,” and “daily use”). Each group was then subdivided into three groups based on total folic acid and dietary folate intake. Outcomes were determined considering the wheeze and eczema status of each child at the age of 2 years. The status was based on the International Study of Asthma and Allergies in Childhood. It was found that 22.1% of the mothers took folic acid supplements daily. In contrast, 56.3% of the mothers did not take these supplements. Maternal intake of folic acid supplements was not associated with wheeze and eczema in the offspring. In contrast, only dietary folate intake was positively associated with wheeze at the age of 2 (adjusted odds ratio, 1.103; 95% confidence interval, 1.003–1.212). However, there is no scientific evidence of a biological mechanism that clarifies this result. Potential confounders such as other nutrition, outdoor/indoor air pollution, and genetic factors may have affected the results. Therefore, further studies on the association between maternal intake of folic acid and allergic symptoms at the age of 3 or above are needed to confirm the results of this study. Trial registration UMIN Clinical Trials Registry (number: UMIN000030786)